2012
DOI: 10.1007/s11892-012-0252-0
|View full text |Cite
|
Sign up to set email alerts
|

Transculturalization of a Diabetes-Specific Nutrition Algorithm: Asian Application

Abstract: The prevalence of type 2 diabetes (T2D) in Asia is growing at an alarming rate, posing significant clinical and economic risk to health care stakeholders. Commonly, Asian patients with T2D manifest a distinctive combination of characteristics that include earlier disease onset, distinct pathophysiology, syndrome of complications, and shorter life expectancy. Optimizing treatment outcomes for such patients requires a coordinated inclusive care plan and knowledgeable practitioners. Comprehensive management start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 44 publications
1
23
1
Order By: Relevance
“…Studies have shown that traditional Asian diets include a larger proportion of carbohydrates (55-70% total energy intake) and a smaller proportion of fat compared with typical Western diets 23 . The carbohydrate component of the diets of the participants in the present study (mean 54% daily energy intake) is consistent with a traditional Asian diet, and is well within the limits (<55-65% daily energy intake) recommended for patients with diabetes in China 24 . This is in contrast to the findings from a previous study, which suggested that most newly diagnosed (less than 3 months) patients with type 2 diabetes mellitus in China consumed a much larger proportion (67% of energy intake) of carbohydrates in their diet 11 .…”
Section: Discussionsupporting
confidence: 79%
“…Studies have shown that traditional Asian diets include a larger proportion of carbohydrates (55-70% total energy intake) and a smaller proportion of fat compared with typical Western diets 23 . The carbohydrate component of the diets of the participants in the present study (mean 54% daily energy intake) is consistent with a traditional Asian diet, and is well within the limits (<55-65% daily energy intake) recommended for patients with diabetes in China 24 . This is in contrast to the findings from a previous study, which suggested that most newly diagnosed (less than 3 months) patients with type 2 diabetes mellitus in China consumed a much larger proportion (67% of energy intake) of carbohydrates in their diet 11 .…”
Section: Discussionsupporting
confidence: 79%
“…However, diabetes dietary guidelines can be cumbersome. Due to their ease of use and previously discussed efficacy, meal or calorie replacements that are also glycemia-targeted have been incorporated as a recommended tool in several diabetesspecific nutritional plans [33,34] and within the recently published Transcultural Diabetes-specific Nutritional Algorithms [4][5][6]. This study demonstrates that breakfast consumption in people with T2DM can be metabolically beneficial when appropriate glycemia-targeted breakfast choices are made and supports the use of GTSN at the breakfast eating occasion as recommended in the Transcultural Diabetes-specific Nutrition Algorithms [4][5][6].…”
Section: Discussion Plasma Blood Glucosementioning
confidence: 99%
“…Medical nutrition therapy is a critical part of globally accepted treatment guidelines for type 2 diabetes mellitus (T2DM) [1][2][3][4][5][6]. An important feature of these nutrition therapeutic guidelines is attention to type and amount of carbohydrate and calorie control leading to weight management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tDNA-PATh toolkit (Figure 22.1) has been validated for content, clinical needs, and utility via survey methodology [31,43,45,47]. This phase includes an in-office toolkit, which is referred to as "tDNA-Patient Algorithm Therapy" (tDNA-PATh), and is the result of a collaborative effort between the tDNA-CIC and Joslin Diabetes Center health services.…”
Section: Tdna Content Validationmentioning
confidence: 99%